The Impact Analysis of Road Deterioration on Road Users and the Surrounding Environment: A Case Study of Sultan Agung Road, Rakam Village, Selong, East Lombok - Muh. Erwin Syah, Ramaedo Ervia Syah; agus, putramuliadi; bqliana, widiyanti (Jurnal Teknologi Lingkungan, 2025)
Sultan Agung Street in Rakam Subdistrict plays a vital role in supporting community mobility and regional economic growth. However, several sections of the road have been severely damaged, which prompted this study to focus on analyzing the effects of road damage along a 1,2 km segment. The purpose of this research is to examine the impacts of road damage on road users and the surrounding environment based on four research variables: health, safety and comfort, economy, and socio cultural aspects. This study employs a descriptive qualitative method with data collected through field observation, measurement, interviews, and documentation. The findings indicate that the condition of Sultan Agung Road at the 1.2 km study location experienced varying degrees of damage, dominated by severe (59.09%) and super-severe damage at (4,55%). This damage impacts community activities, particularly in the areas of health, safety and comfort, economics, and socio cultural aspects. Given these conditions, the community hopes for road repairs, particularly on sections with severe and super severe damage as a top priority.